2010
DOI: 10.1073/pnas.0913302107
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of TcaR and its complexes with multiple antibiotics from Staphylococcus epidermidis

Abstract: TcaR and IcaR are a weak and a strong negative regulator of transcription of the ica locus, respectively, and their presence prevents the poly-N-acetylglucosamine production and biofilm formation in Staphylococcus epidermidis. Although TcaR was shown to interact with the ica promoter, the precise binding region and the mechanism of interaction remained unclear. Here we present the 3D structure of TcaR in its apo form and in complex with salicylate as well as several aminoglycoside and β-lactam antibiotics. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 39 publications
9
79
2
1
Order By: Relevance
“…However, the exact mechanisms involved in enhancing biofilm formation upon exposure to sub-MIC VAN levels in non-Rsp strains are not well known. In contrast to Staphylococcus epidermidis, few studies have examined the effects of sub-MIC antibiotics on S. aureus biofilm formation (14,(41)(42)(43)(44). One recent study reported that sub-MIC VAN levels can enhance S. aureus cell lysis and extracellular DNA release and promote biofilm formation (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanisms involved in enhancing biofilm formation upon exposure to sub-MIC VAN levels in non-Rsp strains are not well known. In contrast to Staphylococcus epidermidis, few studies have examined the effects of sub-MIC antibiotics on S. aureus biofilm formation (14,(41)(42)(43)(44). One recent study reported that sub-MIC VAN levels can enhance S. aureus cell lysis and extracellular DNA release and promote biofilm formation (14).…”
Section: Discussionmentioning
confidence: 99%
“…El aumento de la formación de biopelícula también se ha visto en S. epidermidis a través del aumento de la producción de Pia. Los antimicrobianos formarían un complejo con TcaR (regulador de la transcripción del operon ica) el cual produciría el aumento de expresión 47 . En el locus homólogo de S. epidermidis, la regulación del ica ocurre a través de una inactivación reversible con la inserción de una secuencia (IS256) en 25 a 35% de las variantes 48 .…”
Section: Infectología Al Día Patogeniaunclassified
“…Although the ligand binding sites in ST1710 and MTH313 are comparable, we have not found any conformational changes in ST1710 between the apo and ligand bound complexes, as observed in MTH313. Meanwhile, eight salicylate molecules are bound to Staphylococcus epidermidis of TcaR (Chang et al, 2010). Among these eight molecules, two are bound similarly to that with MTH313, while the other two were observed in the more shallow binding pocket in each monomer.…”
Section: Interactions Between Marr Homologues and Ligandsmentioning
confidence: 99%
“…The remaining ligands are highly exposed to the solvent. TcaR has also been crystallized with four different antibiotics (ampicillin, kanamycin, methicillin and penicillin), revealing their interactions with the protein (Chang et al, 2010 …”
Section: Interactions Between Marr Homologues and Ligandsmentioning
confidence: 99%